2019
DOI: 10.1007/s10295-019-02239-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of O-methylated flavanones from methylated phenylpropanoic acids in engineered Escherichia coli

Abstract: Methylated flavonoids possess improved bioactivities compared to their unmethylated counterparts. In this study, for the efficient production of O-methylated flavonoids from simple methylated phenylpropanoic acids, a recombinant Escherichia coli strain expressing 4-coumarate:coenzyme A ligase (4CL) from Oryza sativa and chalcone synthase (CHS) from Hordeum vulgare was constructed; this strain produced significant amount of homoeriodictyol (~ 52 mg/L) as well as a few amount of hesperetin (0.4 mg/L), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 25 publications
2
34
2
Order By: Relevance
“…Although we only produced 0.5 mg/l homoeriodictyol from our ΔPAL pathways, Cui et al ( 18 ) recently reported the production of 52 mg/l homoeriodictyol by feeding ferulic acid at lower concentrations. Therefore, we investigated the construction of pathways to allow the complete biosynthesis of homoeriodictyol from tyrosine, with the rationale that ferulic acid produced in situ would be quickly converted on to homoeriodictyol, preventing build-up that may inhibit pathway function.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Although we only produced 0.5 mg/l homoeriodictyol from our ΔPAL pathways, Cui et al ( 18 ) recently reported the production of 52 mg/l homoeriodictyol by feeding ferulic acid at lower concentrations. Therefore, we investigated the construction of pathways to allow the complete biosynthesis of homoeriodictyol from tyrosine, with the rationale that ferulic acid produced in situ would be quickly converted on to homoeriodictyol, preventing build-up that may inhibit pathway function.…”
Section: Resultsmentioning
confidence: 71%
“…Automated, worklist-driven liquid handling was implemented for bridging oligo pooling and ligase cycling reaction setup. Completed reactions were transformed into high-efficiency NEB 5-alpha cells, and correct plasmid assemblies identified by high-throughput, next-generation sequencing using Nanopore technology ( 18 ). Some assemblies ( Supplementary Table S3 ) were also verified using Sanger sequencing (GATC Biotech).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cui et al . obtained hesperetin and homoeriodictyol at a low titer in engineered E. coli from fed isoferulic acid and ferulic acid 22 . The enzymes used in that study had previously been shown to have high substrate promiscuity in vitro 43,44 and were then used in vivo for the first time 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The next day, 1mL of the starter culture was inoculated into 50 mL of fresh LB medium. IPTG (final concentration 1mM) was added to the culture broths when the optical density reached 0.4-0.6 for protein expression and the cultures were successively incubated at 30 °C for an additional 3 h. The cells were collected by centrifugation for 30 min at 3,700 rpm (Eppendorf 5920R, Germany) and 4 °C and then resuspended in 25 mL of fresh modified MOPS medium which included 1mM substrate, 1mM IPTG, and 20μg/mL cerulenin for further 32h fermentation 22 .…”
Section: Fermentation Conditionsmentioning
confidence: 99%